Chronic Myeloid Leukemia with Rare e1a3 BCR-ABL Transcript - Najia Tabassum; Rubina Ghani; Mohammad Saboor; Moinuddin Moinuddin (ziauddin University, 2024)
Chronic myelogenous leukemia (CML) results from neoplastic transformation of a hematopoietic stem cell. It is cytogenetically characterized by the presence of Philadelphia chromosome which results from reciprocal translocation t(9;22) that juxtaposes the ABL gene on chromosome 9 with breakpoint cluster region (BCR) on chromosome 22 generating BCR-ABL oncogene. All BCR-ABL fusion proteins display activated tyrosine kinase activity. Their different types are associated with different clinical course and prognosis. We report a rare case of e1a3 BCR-ABL transcript. So far only 4 cases in patients with CML have been reported. Key Words: BCR-ABL, e1a3, CML.